EMERGENCY MANAGEMENT OF CHEST TRAUMA REQUIRING INTUBATION: CLINICAL OUTCOMES AT PUMHS NAWABSHAH. : JPUMHS;2024:14:04,116-1123.http://doi.org/10.46536/jpumhs/2024/14.04.568 - Mohammad Ramzan1, Sajjad Hussain Qureshi2, Mukhtyar Ahmed Abro3, Shahzad Memon4, Noor Nabi Siyal5, Awais Bashir Larik6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Morbidity and mortality from chest trauma, in particular, is a major contributor and occurs especially in low- and middle-income countries LMICs. Emergency tracheal intubation continues to be a cornerstone of airway management for critically injured patients, but outcomes are variable depending upon the type, timing, and complications of intubation. This study assesses the clinical outcomes of emergency intubation in chest trauma patients treated at PUMHS Nawabshah. METHODS: This is a cross-sectional study with 120 patients with chest trauma who need emergency intubation. Demographics, mechanisms of injury, time to intubation, method direct vs. video laryngoscopy, complications, mortality and hospital length of stay were noted. Chi-square tests, Kaplan-Meier survival analysis and logistic regression were used to identify predictors of mortality. RESULTS: Male patients made up the majority of patients 76.7% and the commonest mechanism of injury was road traffic accidents 60%. There was a significant increase in mortality with delay to intubation, from 5% 5–10 minutes to 16.7% >20 minutes p=0.045. Although in widespread use 75%, direct laryngoscopy was associated with higher rates of hypoxia 20% than video laryngoscopy. Airway trauma patients averaged 11.5 days in the hospital and complications with hypoxia and hypotension prolonged hospital stay. Time to intubation and length of stay were identified as significant predictors of mortality p<0.01 by logistic regression. CONCLUSION: Chest trauma patients require timely intubation and effective airway management to improve outcomes. There are efforts to decrease delays and operator proficiency in advanced airway techniques to reduce complication and mortality.